A novel mutual authentication scheme with formal proof for smart healthcare systems under global mobility networks notion. (May 2018) - Wu, Fan; Li, Xiong; Xu, Lili; Kumari, Saru; Sangaiah, Arun Kumar
Abstract: Smart healthcare is an emergent part in modern telemedical technology. To solve the problem of collecting information from roaming patients, global mobility network (GLOMONET) is a good way for data transferring. It is common sense that wireless circumstance is full of attacks, and the case how to protect the wireless network away from danger attracts researchers. We present a new two-factor authentication scheme for GLOMONETs to vanquish the hazard. Then the formal proof demonstrates that the attacker can crack the session key and the privacy of the scheme with a negligibly higher probability than directly guessing the password. Moreover, according to the informal analysis model, our scheme meets all the security properties. Finally, via performance comparison and network communication simulation by NS-3, our scheme is fit for practicality.